Anti-reflection effect of large-area ZnO nano-needle array on multi-crystalline silicon solar cells. (February 2022) - Wang, Meihuizi; He, Haiyan; Shou, Chunhui; Cui, Hao; Yang, Deren; Wang, Lei
Abstract: The current diamond-wire-sawed multi-crystalline silicon wafer lacks an effective light trapping structure, which results in high reflectivity and hinders the improvement of efficiency. In this work, we proposed an enhanced light trapping structure outside the junction of multi-crystalline silicon solar cells, that is, constructing a ZnO nano-needle array on the surface of the textured multi-crystalline silicon to minimize the reflection in the visible-near infrared band to achieve light trapping effect. Solar cells with ZnO nano-needle structure exhibit excellent light trapping performance over a wide band (350–1100 nm). The low-cost and simple preparation method makes this enhanced light trapping structure has broad application prospects. Highlights: Enhanced light trapping structure outside the multi-crystalline silicon solar cell. Unique refractive index gradient structure with good light trapping effect. Simple and low-cost preparation method.